Significant gender-specific difference in brain lateralization of schizophrenia patients assessed by new combined foot dominance scale - Akabalieva, Katerina (Frontiers in Psychiatry, 2023)
Objective: Reduced hemispheric asymmetry has been identified as a potential risk factor for schizophrenia, characterized by diminished brain lateralization and a lack of dominance in the left hemisphere. Moreover, there is growing evidence of disrupted connectivity between various cortical regions. This study aimed to investigate gender differences in left-footedness as a potential biological marker for neuronal dysontogenesis in individuals with schizophrenia and control subjects. Material and methods: A New Combined Foot Dominance Scale (14 foot tests), comprising a Modified Chapman & Chapman Subscale (10 foot tests) and a Complex Tasks Subscale (4 foot tests) was administered as performance tasks in 180 subjects (98 schizophrenia patients with mean age 34.45 years (SD=15.67, range 23-79) for men and 42.20 years (SD=11.38, range (21-63) for women and 82 controlsl with a mean age 34.70 years (SD=16,82, range 18-79) for men and 44.50 years (SD=10.73, range 23-67) subjects. As our data is not continuous and lacks normal distribution, the non-parametric Mann-Whitney test was used for comparing categorical data.The mean left-footedness, as assessed by the New Combined Foot Dominance Scale, is significantly higher in individuals with schizophrenia compared to control subjects. Our findings from inter-gender comparisons reveal that female schizophrenia patients exhibit a significantly greater average left-footedness than female control subjects, while in males no such a statistical significant difference is detectedthis difference is less pronounced in males. Conclusions: Schizophrenia is characterized by abnormal brain asymmetry and a lack of dominance in the left hemisphere, leading to compromised lateralized functions. Importantly, these effects show a distinct pattern specific to each gender. Left foot dominance is higher in patients with schizophrenia than in control subjects and women contribute significantly more to this difference. emerges as a promising indicator of altered hemispheric lateralization, as it is minimally influenced by cultural and traditional factors and reveals notable sex-specific differences.